(untitled) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2025)
Caijia is a very interesting Sino-Tibetan language variety. It has been documented only recently, it seems to belong to the Sinitic branch of Sino-Tibetan, but shows some archaic features that have led to some controversies among scholars regarding its proper affiliation, and detailed comparative analyses of the language in comparison with other Sino-Tibetan languages are still in their infancy. This little study demonstrates how a first published wordlist of Caijia (Lee 2023) can be prepared for the inclusion in the Lexibank repository.